Cohesion and Coherence: An Analysis of the Students’ Narrative Writings - Egi Dwi Putra; Heri Samudra; Ani Susanti (Universitas Muhammadiyah Kalimantan Timur, 2022)
The research was conducted to analyze cohesion and coherence used on 20 student’s narrative writing in SMAN 4 Praya. Descriptive qualitative method used in this research by collecting data from students narrative writing assignments. Then, classifying the findings by using the theory introduced by Halliday and Hasan (1976). The results obtained from the data were: (a) grammatical cohesion; reference 61.09%, substitution 13.53%, ellipsis 04.88%, and conjunction 26.50%; 2) lexical cohesion; repetition 72%, synonym 18%, and collocation 10%. (b) the students’ produced coherence of the narratives; the development of themes and generic structure. The data shows that students were able to organize their ideas cohesively and coherently. It is evident that the students’ writing ability was sufficiently developed by using cohesion and coherence devices.